Algoritmo em GPGPU para Acelerar a Determinação do Campo Acústico Produzido por Transdutor Ultrassônico Circular com Excitação Contínua (2020)
This work presents a GPU algorithm to calculate the acoustic field generated by a circular ultrasonic transducer radiating in water a continuous wave. The acoustic pressure in a space point in front of the transducer is calculated by Rayleigh integral, which uses the Huygens principle to compose the field as the sum of contributions from an infinite number of point sources. Because the pressure at each spatial point can be calculated independently, the solution algorithm can run in parallel, taking advantage of the GPU cores. Some experiments were performed in a frequency range from 0.25 to 5.0 MHz. The radiating surface was discretized in order to have a fixed number of elemental areas per wavelength. Results showed the validity of the acoustic fields simulated. In addition, a performance analysis showed that the GPU was 50 times faster than CPU for the most demanding problems.